Engineering Carbon Materials for Electrochemical Oxygen Reduction Reactions. Issue 32 (14th July 2021) - Lin, Liangxu; Miao, Naihua; Wallace, Gordon G.; Chen, Jun; Allwood, Dan A.
Abstract: The electrochemical oxygen reduction reaction (ORR) is the key energy conversion reaction involved in fuel cells, metal‐air batteries, and hydrogen peroxide production. Proliferation and improvement of the ORR requires wider use of new and existing high performance catalysts; unfortunately, most of these are still based on precious metals and become uneconomical in mass‐use applications. Recent progress suggests that low cost and durable carbon materials can potentially be developed as efficient ORR catalysts. Significant efforts have been made in discovering fundamental catalytic mechanisms and engineering techniques to guide and enable viable regulation of both the ORR activity and selectivity of these carbon catalysts. Starting from the fundamental understanding, this report reviews recent progress in engineering carbon materials from exotic chemical doping to intrinsic geometric defects for improved ORR. On the basis of both theoretical and experimental investigations reported so far in this area, future improvements in carbon catalysts are also discussed, providing useful pathways for more efficient and reliable energy conversion technologies. Abstract : Building on fundamental understandings of the electrochemical oxygen reduction reaction (ORR), the key engineering strategies of carbon materials for the improved ORR are critically reviewed, providing clear and straightforward pathways towards the improved ORR with regulable activity and selectivity.